Ayurvedic Management Of Psoriasis W.S.R Ekkustha: A Case Study (International Journal of Environmental Sciences, 2025)
In most of ayurvedic texts, all types of kustha have been considerd as rakta pradosaj vikara, further ekkustha is stated to be tridosaj with the dominance of vat kaph dosha and twacha as dosha adhisthan. It is a type of kchudra kustha occurring mainly due to imbalance of vat kaph dosha and resembling psoriasis in its clinical manifestation, primarily with cardinal symptoms as loss of perspiration in a large skin area with silvery scaly lesions, like scales of a fish (in majority of classics). Brihtrayi have mentioned its chikitsa as sodhan followed by shamshaman and rasayan chikitsa.This case study is all about treatment of ekkustha given to a psoriatic patient and its positive relief.